2017
DOI: 10.1038/hortres.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

VqMAPKKK38 is essential for stilbene accumulation in grapevine

Abstract: Vitis species, including grapevine, produce a class of secondary metabolites called stilbenes that are important for plant disease resistance and can have positive effects on human health. Mitogen-activated protein kinase (MAPK) signaling cascades not only play key roles in plant defense responses but also contribute to stilbene biosynthesis in grapevine. MAPKKKs function at the upper level of the MAPK network and initiate signaling through this pathway. In this study, a Raf-like MAPKKK gene, VqMAPKKK38, was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…In wheat, a MAPKKK named TaFLR can be activated by the leaf rust pathogen Puccinia triticina [31]. In grapevine, VqMAPKKK38 can be highly induced by powdery mildew infection [32]. All the evidence suggests that members of MAPKKKs are essential in pathogen attack signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, a MAPKKK named TaFLR can be activated by the leaf rust pathogen Puccinia triticina [31]. In grapevine, VqMAPKKK38 can be highly induced by powdery mildew infection [32]. All the evidence suggests that members of MAPKKKs are essential in pathogen attack signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, a MAPKKK named TaFLR can be activated by the leaf rust pathogen Puccinia triticina [40]. While in grapevine, VqMAPKKK38 can be highly induced by powdery mildew infection [41]. All the evidence suggests the members of MAPKKKs are essential in pathogen attack signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in the sterile cultivated tissues of JWB plantlets, four ZjMAPKKKs (4, 10, 25 and 44) were significantly induced in the diseased plants. Also,ZjMAPKKK6,7,17,18,30,34,35,37,40,41,43,46,52…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results highlight the intricate signaling pathways in which calcium is involved and the interplay with other signaling processes. Accordingly, recent studies demonstrated that calcium can modulate stilbene biosynthesis in Vitis, in mechanisms that require the involvement of calcium-dependent and mitogen-activated protein kinases (Aleynova et al, 2015;Jiao et al, 2017). Few studies on Arabidopsis, strawberry and grape also suggested a link between calcium and anthocyanins, where Ca 2+ , calmodulin, sugars, and protein kinases/phosphatases are key players, possibly by modulating anthocyanin biosynthetic genes (Vitrac et al, 2000;Shin et al, 2013;Xu et al, 2014;Peng et al, 2016;Zou et al, 2017).…”
Section: Calcium-hormone Interplay Regulates Key Enzymes Involved In mentioning
confidence: 99%